The Effect of Working Capital Turnover and Debt to Equity Ratio on Profitability at PT. Adhi Karya Tbk. (Listed on the Indonesia Stock Exchange for the 2015-2022 Period) - Fauziah, Siti; Purnama, Reka Ardian (Formosa Journal of Sustainable Research, 2024)
This study was conducted to determine the influence of This descriptive quantitative study investigates the financial performance of PT. Adhi Karya, Tbk. from 2015 to the present by looking at working capital and debt to equity ratio. until 2022. This study uses a saturated sample technique of 32, and the data was analyzed using the classical assumption test hypothesis test, correlation analysis, coefficient of determination, regression analysis, and conducting Hypothesis testing was carried out The results of the partial significance test, which was carried out with SPSS version 24.0, showed that the number of 7.848 was greater than 2.045, indicating that the working capital turnover factor affects profitability. partially. In conclusion, this shows that the working capital turnover factor affects overall profitability. partially. The debt ratio variable has a negative impact on profitability, because T calculates the debt ratio of -3.217 less than the t table of -2.045. Furthermore, the hypothesis is obtained to be tested simultaneously. With a calculated f value of 40.855, a t table value of 0.000, and a sig value (p value) of 0.000 3.328, working capital turnover and the ratio of debt to equity have a positive impact on profits